STUDI FENOMENOLOGI ATAS IMPLEMENTASI AKUNTANSI BERBASIS AKRUAL PADA BADAN LAYANAN UMUM DAERAH RSUD DR. SAIFUL ANWAR MALANG - Rachmawati Rachmawati; Ali Djamhuri; Wuryan Andayani (Universitas Negeri Malang, 2018)
This research is aimed to obtain deep understanding about the meaning of accrual based accounting implementation based on financial management experience in Saiful Anwar hospital. Through Husserl's phenomenology, the implementation of accrual-based accounting is interpreted as